The Contribution of Self-Concept and Parental Support towards Learning Motivation of The Students who were Expelled from Their Previous Schools - Yogi Sefra Joni; Mudjiran Mudjiran; Yanuar Kiram (Journal of Educational and Learning Studies, 2019)
Underlying this present study was the importance of increasing the learning motivation of students who were expelled from previous schools. Self-concept and parental support were considered as the factors affecting learning motivation of the students who were expelled from previous schools. The aimed of this study was to reveal the contribution of self-concept and parental support towards the learning motivation of the students who were expelled from their previous schools. This study used a descriptive correlation-quantitative method. The population of the study were the 11th and 12th grade students in Sungai Penuh City, which numbered 2666 in total. The samples of the study were 62 students, taken by purposive sampling technique, namely students who were expelled from the previous schools. The instrument used was a Likert scale. The research findings showed that self-concept and parental support respectively and simultaneously had a significant contribution to the learning motivation of the students who were expelled from their previous school.